2012
DOI: 10.1249/mss.0b013e3182351913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Activity Monitors in Controlled and Free-Living Environments

Abstract: We demonstrated that BMI does not affect the step output of commonly used activity monitors during walking. In addition, 67 m·min⁻¹ seems to be the minimum speed required for accurate step counting, at least for most waist-mounted activity monitors. Finally, the StepWatch, AG7164, and activPAL™ were the most accurate devices on the TM, but only the AG7164 yielded comparable step counts to the StepWatch in the free-living environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 37 publications
7
119
1
3
Order By: Relevance
“…However, the findings are equivocal, with studies finding good agreement between these two methods [27][28][29] and others showing weak concordance, specifically because GT3X output of count thresholds is less sensitive to detect sitting/standing transitions compared to ActivPAL [6,30]. These controversial results can be partially explained by the variability in studies' conditions (laboratory or free-living), and the fact that previous studies have used different cutoffs to define sedentary time when using accelerometry.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings are equivocal, with studies finding good agreement between these two methods [27][28][29] and others showing weak concordance, specifically because GT3X output of count thresholds is less sensitive to detect sitting/standing transitions compared to ActivPAL [6,30]. These controversial results can be partially explained by the variability in studies' conditions (laboratory or free-living), and the fact that previous studies have used different cutoffs to define sedentary time when using accelerometry.…”
Section: Discussionmentioning
confidence: 99%
“…During Furlanetto et al's study subjects walked on a treadmill and gait and energy requirements differ from those required during free walking on the ground perhaps not providing a true reflection of domestic physical activity. 19,20 Importantly, standardized walking speeds were not applied and subjects were only monitored for one min meaning a constant pace of walking could not have been reached. 18 These considerations made it difficult to conclude if the SWM could distinguish between walking speeds.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 Furthermore, it has been demonstrated that the reliability of activity monitoring depends on disease severity and the number of days used for analysis. Future research needs to focus on the development of accurate guidelines regarding activity monitoring in order to standardize research protocols so comparisons between different populations can be made more easily.…”
Section: Future Researchmentioning
confidence: 99%
“…The SAM has been validated for use in patients with COPD 32 and is highly accurate in measuring steps across a range of speeds compared with other accelerometers on the market. [33][34][35] Participants were asked to wear the SAM during waking hours for 7 days. The SAM was programmed to record in 1-min epochs; a valid day was defi ned as having Ն 10 h (600 min) of monitor wear.…”
Section: Multivariate Regression Modelsmentioning
confidence: 99%